Dual-band all-dielectric chiral photonic crystal. (21st April 2022) - Du, Lianlian; Liu, Yahong; Zhou, Xin; Tao, Liyun; Li, Meize; Ren, Huiling; Ji, Ruonan; Song, Kun; Zhao, Xiaopeng; Navarro-Cía, Miguel
Abstract: We present an all-dielectric chiral photonic crystal that guides the propagation of electromagnetic waves without backscattering for dual bands. The chiral photonic crystal unit cell is composed of four dielectric cylinders with increasing inner diameter clockwise or anticlockwise, which leads to chirality. It is demonstrated that the proposed chiral photonic crystal can generate dual band gaps in the gigahertz frequency range and has two types of edge states, which is similar to topologically protected edge states. Hence, the interface formed by the proposed 2D chiral photonic crystal can guide the propagation of electromagnetic waves without backscattering, and this complete propagation is immune to defects (position disorder or frequency disorder). To illustrate the applicability of the findings in communication systems, we report a duplexer and a power divider based on the presented all-dielectric chiral photonic crystal.